The effects of photographic and textual framing on public support and risk perception of controversial and non-controversial sciences - Lee, Edmund Wei Jian (2014)
Studies on framing have shown that how the media frame an issue can significantly impact public perception and acceptance of science and emerging technologies. However, many of these studies have examined textual framing without considering the role of photographs in the framing process. This study seeks to fill the research gap by laying a conceptual framework for photographic framing and test the impact of either framing types on public support and risk perception of a controversial (nuclear energy) and a non-controversial science topic (nanotechnology) in Singapore.